Lunar and Planetary Science XV : abstracts of papers submitted to the fifteenth Lunar and Planetary Science Conference, March 12-16, 1984 (Lunar and Planetary Institute, 1984)
You must extract the zipped files before using. To begin viewing the abstracts, click on the file "index.html." Various papers on lunar and planetary science are presented. The general topics addressed include: lunar highlands and early evolution; lunar regoliths, exposure, and impact processes; lunar volcanic gases; lunar luminescence; meteorite studies; Mars, tektites, and comets. Sponsored by Lunar and Planetary Institute, NASA/Johnson Space Center, American Geophysical Union, Division for Planetary Science of the American Astronomical Society, Geological Society of America, and the Meteoritical Society. PARTIAL CONTENTS: Inversion of Topography in Martian Highlands Terrains / de Hon, R.A. -- Why did so Many Polymict Eucrites Land and Survive Only in Antarctica? / Delaney, J.S. -- Vesicles in Four Varieties of Apollo 15 Volcanic Glass / Delano, J.W. -- Quenching Effects on Iron Site Partitioning in the Apollo 17 Orange Glass Composition / Dyar, M.D. -- Volcanoes of the Kane Patera Quadrangle of io Classified by Proportions of Lava Flows to Pyroclastic Flows / Elston, W.E.